A floristic analysis of the lowland dipterocarp forests of Borneo - Slik, J.W.F.; Poulsen, A.D.; Ashton, P.S.; Cannon, Charles H.; Eichhorn, K.A.O.; Kartawinata, K.; Lanniari, I.; Nagamasu, H.; Nakagawa, M.; Nieuwstadt, M.G.L. van; Payne, J.; Purwaningsih; et al. (2003)
The aim of this paper is to (1) identify floristic regions in the lowland (below 500 m a.s.l.) tropical dipterocarp rain forest of Borneo based on tree genera, (2) determine the characteristic taxa of these regions, (3) study tree diversity patterns within Borneo, and (4) relate the floristic and diversity patterns to abiotic factors such as mean annual rainfall and geographical distance between plots. Results: A total of 77 families and 363 genera were included in the analysis. On average a random sample of 640 trees from a lowland dipterocarp forest in Borneo contains 41.6 3.8 families and 103.0 12.7 genera. Diversity varied strongly on local scales. On a regional scale, diversity was found to be highest in south-east Borneo and central Sarawak. The most common families were Dipterocarpaceae (21.9% of trees) and Euphorbiaceae (12.2% of trees). The most common genera were Shorea (12.3% of trees) and Syzygium (5.0% of trees). The 28 locations were clustered in geographically distinct floristic regions. This was related to the fact that floristic similarity depended strongly on the geographical distance between plots and similarity in mean annual rainfall.